Craft techniques & projects - Masciocchi, Corinne; Mandleberg, Hilary (DK Pub., 2012)
"The most comprehensive how-to craft guide available, this authoritative book covers all the most popular crafts and includes beautiful, contemporary projects."--P. [4] of co